Can actigraphy be used to define lithium response dimensions in bipolar disorders? - Etain, Bruno; Meyrel, Manon; Hennion, Vincent; Bellivier, Frank; Scott, Jan (Journal of Affective Disorders, 2021)
Background: Actigraphy is commonly used in case-control studies to explore sleep-wake patterns and circadian rhythmicity in bipolar disorders (BD). However, there is limited ecological research regarding actigraphy parameters associated with response to lithium (Li_Resp).Methods: Outpatients with BD-I (n=70) and BD-II (n=20) who were all prescribed prophylactic Li undertook 21 consecutive days of actigraphy recording. The Retrospective Assessment of Response to Lithium Scale (also referred as the Alda scale) was rated on a 0-10 continuum. We used principal component analysis (PCA) to summarize interrelationships among clinical and actigraphic variables and Li_Resp.Results: PCA demonstrated the existence of a Li_Resp dimension (accounting for >20% explained variance) characterized by 5 markers of circadian timing and rhythmicity. Replication of the PCA, using the resampling procedure, confirmed this model was robust for the BD-I but not for BD-II (which showed weaker associations between Li_Resp and sleep variables). These circadian rhythm markers identified by PCA correctly classified 64% (95% Confidence Intervals: 52-76%; p<0.03) of all BD cases as Li responders or non-responders.Limitations: Although we attempted to minimize risk of statistical error, the small BD-II subsample may have undermined the ability of PCA to identify a robust Li_Resp dimension for this subtype.Conclusions: Our findings are compatible with circadian models of BD and with putative mechanisms of action of Li. If confirmed in prospective studies, the study offers support for use of actigraphy as a relevant method for real time objective monitoring of Li_Resp, with few concerns regarding reliability and validity.